Mutations in IRS4 are associated with central hypothyroidism. Issue 10 (30th July 2018) - Heinen, Charlotte A; de Vries, Emmely M; Alders, Mariëlle; Bikker, Hennie; Zwaveling-Soonawala, Nitash; van den Akker, Erica L T; Bakker, Boudewijn; Hoorweg-Nijman, Gera; Roelfsema, Ferdinand; Hennekam, Raoul C; Boelen, Anita; van Trotsenburg, A S Paul; et al.
Abstract : Background: Four genetic causes of isolated congenital central hypothyroidism (CeH) have been identified, but many cases remain unexplained. We hypothesised the existence of other genetic causes of CeH with a Mendelian inheritance pattern. Methods: We performed exome sequencing in two families with unexplained isolated CeH and subsequently Sanger sequenced unrelated idiopathic CeH cases. We performed clinical and biochemical characterisation of the probands and carriers identified by family screening. We investigated IRS4 mRNA expression in human hypothalamus and pituitary tissue, and measured serum thyroid hormones and Trh and Tshb mRNA expression in hypothalamus and pituitary tissue of Irs4 knockout mice. Results: We found mutations in the insulin receptor substrate 4 ( IRS4 ) gene in two pairs of brothers with CeH (one nonsense, one frameshift). Sequencing of IRS4 in 12 unrelated CeH cases negative for variants in known genes yielded three frameshift mutations (two novel) in three patients and one male sibling. All male carriers (n=8) had CeH with plasma free thyroxine concentrations below the reference interval. MRI of the hypothalamus and pituitary showed no structural abnormalities (n=12). 24-hour thyroid-stimulating hormone (TSH) secretion profiles in two adult male patients showed decreased basal, pulsatile and total TSH secretion . IRS4 mRNA was expressed in human hypothalamic nuclei, including the paraventricular nucleus, and in the pituitary gland. Female knockout mice showed decreased pituitary Tshb mRNA levels but had unchanged serum thyroid hormone concentrations. Conclusions: Mutations in IRS4 are associated with isolated CeH in male carriers. As IRS4 is involved in leptin signalling, the phenotype may be related to disrupted leptin signalling.